Tantangan Dan Strategi Pendidikan Inklusif Dalam Mempersiapkan Siswa Adhd Menghadapi Tantangan Revolusi Industri 4.0 - Qorie Hizratul Muttaqien; Ayub Suganda; Wisnu Hambali Hidayat; Naufal Abdillah; Tarsono (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
Inclusive education is an approach that ensures the right of every child, including those with special needs, to receive equitable education in an environment that supports diversity. This concept is based on principles of equality, acceptance of differences, and the elimination of discrimination, as outlined in various international documents such as the Salamanca Statement and the Universal Declaration of Human Rights (1948). The Fourth Industrial Revolution offers opportunities through technological integration but also presents specific challenges for students with Attention Deficit Hyperactivity Disorder (ADHD). Comprehensive strategies are needed to address these challenges, including individualized learning approaches, the use of interactive technology, and collaboration among parents, teachers, and the government. Supportive inclusive policies, the development of disability-friendly infrastructure, and the active involvement of the community and parents are essential elements for the success of inclusive education. With these integrated measures, inclusive education is expected to prepare students with special needs to meet the demands of the digital era and achieve their full potential.